Semen Analysis in Cancer Patients Referred for Sperm Cryopreservation before Chemotherapy over a 15-Year Period in Korea - Ku, Ja Yoon; Park, Nam Cheol; Jeon, Tae Gyeong; Park, Hyun Jun (The world journal of men's health, 2015)
This study evaluated the demographics and semen parameters of males with cancer who banked their sperm prior to chemotherapy. This is a retrospective study of 66 cases referred for sperm banking prior to initiation of chemotherapy over a 15-year period (1999~2014). Patients who had previously received cancer treatment including chemotherapy or radiotherapy were not included in this study. We studied a total of 66 cancer patients referred for cryopreservation of sperm prior to chemotherapy. The mean age of the patients at the time of banking was 32.0±7.9 years (range, 19~58 years). The types of cancer were testicular cancer (31 cases, 47.0%), non-Hodgkin's disease (10 cases, 15.1%), Hodgkin's disease (5 cases, 7.6%), leukemia (8 cases, 12.1%), gastrointestinal malignancy (5 cases, 7.6%), and musculoskeletal malignancy (5 cases, 7.6%). There were significant differences in sperm concentration and viability among the various types of cancer, but no significant difference in semen volume or sperm motility and morphology. In this study we found that sperm quality could decrease even before chemotherapy. Because chemotherapy can also negatively affect spermatogenesis, sperm cryopreservation prior to treatment should be strongly recommended for cancer patients of reproductive age.